A light-duty truck model for the analysis of on-center handling characteristics. Issue 2 (9th March 2022) - Duan, Yupeng; Zhang, Yunqing; Wang, Yan; Zeng, Jiongli; Xu, Peijun
For commercial vehicles, on-center handling characteristics deeply influences the driving safety and driver's feeling about the vehicle on highway. This research focuses on the on-center handling performance of light-duty trucks. A vehicle model was built to conduct the simulation of the on-center handling test, which consists of a power steering system, non-independent front/rear suspensions, the powertrain system, and a cab. Nonlinear properties of the power steering system, the friction hysteretic characteristic in the steering system, suspension system with leaf springs are considered so as to reflect the complicated on-center handling characteristics. We conducted constant radius cornering tests, return-release tests, and high speed weave tests on a target vehicle. By comparing the test and simulation results, adjustments were made to the model parameters to improve simulation accuracy. A number of variables were altered to show its influence on the steering feel and vehicle response and results are given out.